Effects of power and hand–eye coordination on volleyball smash accuracy of vocational students - Wangi Daratista; Gusril Gusril; Muhamad Sazeli Rifki; Yuni Astuti (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims investigated the effects of arm muscle power, leg muscle power, and hand–eye coordination on smash accuracy among male volleyball players at SMK Negeri 2 Kerinci. The research employed a quantitative design using path analysis to examine direct, indirect, and simultaneous relationships among variables. The population consisted of 30 male volleyball athletes, with total sampling applied. Arm muscle power was measured using the one-hand medicine ball put test, leg muscle power using the vertical jump test, hand–eye coordination using the ball werfen und fangen test, and smash accuracy through a standardized smash accuracy test. Data were analyzed using path analysis at a significance level of α = 0.05. The results showed that arm muscle power, leg muscle power, and hand–eye coordination each had significant direct effects on smash accuracy, with hand–eye coordination contributing the strongest influence. In addition, arm and leg muscle power exerted significant indirect effects on smash accuracy through hand–eye coordination. Simultaneously, all variables explained a substantial proportion of variance in smash accuracy. These findings highlight the importance of integrating physical power and coordination training in volleyball instruction at the school level.